2011
DOI: 10.1186/1475-2891-10-48
|View full text |Cite
|
Sign up to set email alerts
|

Cholesterol-raising diterpenes in types of coffee commonly consumed in Singapore, Indonesia and India and associations with blood lipids: A survey and cross sectional study

Abstract: BackgroundTo measure the content of cholesterol-raising diterpenes in coffee sold at the retailer level in Singapore, Indonesia and India and to determine the relationship of coffee consumption with lipid levels in a population-based study in Singapore.MethodsSurvey and cross-sectional study in local coffee shops in Singapore, Indonesia and India to measure the diterpene content in coffee, and a population-based study in Singapore to examine the relationship of coffee consumption and blood lipid levels. Interv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
1
7

Year Published

2012
2012
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(32 citation statements)
references
References 23 publications
0
24
1
7
Order By: Relevance
“…Moreover, abstinence from coffee for at least 6 weeks will lower cholesterol concentrations in the general population (Christensen and others ) and in hypercholesterolemic patients (Forde and others ). This negative effect of coffee on cholesterol concentrations, particularly from boiled coffee, is owing to higher concentrations of diterpenes (kahweol and cafestol) in such coffee preparations (deGroot and others ; Gross and others ; Naidoo and others ). However, 4 randomized controlled trials have shown that diterpenes have lipoprotein(a)‐reducing potential, but the authors concluded that their well‐known adverse side effects on LDL cholesterol preclude their use as such (Urgert and others ).…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, abstinence from coffee for at least 6 weeks will lower cholesterol concentrations in the general population (Christensen and others ) and in hypercholesterolemic patients (Forde and others ). This negative effect of coffee on cholesterol concentrations, particularly from boiled coffee, is owing to higher concentrations of diterpenes (kahweol and cafestol) in such coffee preparations (deGroot and others ; Gross and others ; Naidoo and others ). However, 4 randomized controlled trials have shown that diterpenes have lipoprotein(a)‐reducing potential, but the authors concluded that their well‐known adverse side effects on LDL cholesterol preclude their use as such (Urgert and others ).…”
Section: Resultsmentioning
confidence: 99%
“…In Singapore, coffee grounds are typically boiled in water and then filtered through a muslin bag, a process that results in brewed coffee that has similar concentrations of the diterpenes kahweol and cafestol relative to the use of a paper filter, as in most Western populations (10, 17). In a meta-analysis of 6 cohort and 16 case-control studies, Botelho et al .…”
Section: Introductionmentioning
confidence: 99%
“…Controversies regarding its risks and benefits still exist as substances in coffee may have either unfavorable or beneficial effects on the cardiovascular system. 1 A large body of epidemiology studies, including recent studies, [2][3][4][5] examining the association between coffee consumption and serum lipids have yielded inconsistent results.…”
Section: Introductionmentioning
confidence: 99%
“…Controversies regarding its risks and benefits still exist as substances in coffee may have either unfavorable or beneficial effects on the cardiovascular system. 1 A large body of epidemiology studies, including recent studies, [2][3][4][5] examining the association between coffee consumption and serum lipids have yielded inconsistent results.A meta-analysis of nine randomized controlled trials (RCTs) published before December 1998 concluded that consumption of unfiltered, but not filtered, coffee increased serum levels of total cholesterol (TC) and low-density lipoprotein cholesterol (LDL-C). 6 However, this meta-analysis was only based on English-language literature and the authors failed to include two important RCTs, 7,8 which included 345 participants.…”
mentioning
confidence: 99%